Manual de dispensación al alta hospitalaria en el servicio de maternidad del hospital Víctor lazarte Echegaray 2016 - Tocas Bringas, Kevin Franklin (2019)
The dispensing of medicines is a service of great importance in the daily professional practice of any pharmacist who is dedicated to clinical practice and care. Therefore, it was considered to systematize the information and to frame it in a manual, it is of itself useful in the field of public health. To this end, the following objectives were set: to elaborate a dispensing manual for hospital discharge in the maternity service of the Víctor Lazarte Echegaray 2016 hospital, to systematize the dispensing activities in a flow chart as well as to prepare a single format for discharging at hospital discharge in the hospital. maternity service of the Víctor Lazarte Echegaray 2016 hospital. The method consisted of a search for information, selection of information and preparation of the manual. In the end, the proposed objectives of preparing a dispensing manual for hospital discharge in the maternity service of the Víctor Lazarte Echegaray 2016 hospital were obtained. A flowchart was also proposed that synthesizes and simplifies procedures, as well as a unique format for dispensing. at hospital discharge